Bullying Perpetration and Victimization as Externalizing and Internalizing Pathways: A Retrospective Study Linking Parenting Styles and Self-Esteem to Depression, Alcohol Use, and Alcohol-Related Problems. (2nd January 2016) - Luk, Jeremy W.; Patock-Peckham, Julie A.; Medina, Mia; Terrell, Nathan; Belton, Daniel; King, Kevin M.
ABSTRACT: Background: Emerging research suggests significant positive associations between bullying and substance use behaviors. However, these studies typically focused either on the link between substance use and bullying perpetration or victimization, and few have conceptualized bullying perpetration and/or victimization as mediators.Objective: In this study, we simultaneously tested past bullying perpetration and victimization as mediational pathways from retrospective report of parenting styles and global self-esteem to current depressive symptoms, alcohol use, and alcohol-related problems.Methods: Data were collected from a college sample of 419 drinkers. Mediation effects were conducted using a bias-corrected bootstrap technique within a structural equation modeling framework.Results: Two-path mediation analyses indicated that mother and father authoritativeness were protective against bully victimization and depression through higher self-esteem. Conversely, having a permissive or authoritarian mother was positively linked to bullying perpetration, which in turn, was associated with increased alcohol use, and to a lesser degree, more alcohol-related problems. Mother authoritarianism was associated with alcohol-related problems through depressive symptoms. Three-path mediation analyses suggested a trend in which individuals with higher self-esteem were less likely to report alcohol-related problems through lower levels of bullying victimization and depression.Conclusions/Importance: Results suggested that bullying perpetration and victimization may, respectively, serve as externalizing and internalizing pathways through which parenting styles and self-esteem are linked to depression and alcohol-related outcomes. The present study identified multiple modifiable precursors of, and mediational pathways to, alcohol-related problems which could guide the development and implementation of prevention programs targeting problematic alcohol use.